2009
DOI: 10.1007/s11130-009-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antioxidant and Anti-inflammatory Potential in Mice Consuming Sour Cherry Juice (Prunus Cerasus cv. Maraska)

Abstract: The present investigation tested the in vivo antioxidant efficacy (superoxide dismutase, SOD; catalase, CAT; glutathione peroxidase; Gpx), lipid peroxidation (LPO) and anti-inflammatory properties (cyclooxygenase-2; COX-2) of sour cherry juices obtained from an autochthonous cultivar (Prunus cerasus cv. Maraska) that is grown in coastal parts of Croatia. Antioxidant potential was tested in mouse tissue (blood, liver, and brain), LPO (liver, brain) and anti-inflammatory properties in glycogen elicited macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 30 publications
2
40
0
2
Order By: Relevance
“…Sour cherries (Prunus cerasus L) (also called tart cherries) are an important source of anthocyanins and other phytochemicals that possess many potential biological properties (Damar et al, 2012;Šarić et al, 2009). Studies have demonstrated that sour cherries exhibit anticarcinogenic effect in various colon cancer models (Ferreti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sour cherries (Prunus cerasus L) (also called tart cherries) are an important source of anthocyanins and other phytochemicals that possess many potential biological properties (Damar et al, 2012;Šarić et al, 2009). Studies have demonstrated that sour cherries exhibit anticarcinogenic effect in various colon cancer models (Ferreti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study discovered that some natural products could ameliorate antioxidant responses and the inflammatory response in LPS-stimulated macrophages [9,15,16]. Sesamun indicum, Linn.…”
Section: Introductionmentioning
confidence: 99%
“…The red skin and flesh of this fruit contain anthocyanins which have strong antioxidant and anti-inflammatory activities. Cherries were found to have anti-inflammatory effects, increase the antioxidant status and inhibit intestinal tumor development in ApcMin mice and reduce proliferation of human colon cancer cells [11][12][13]. In hyperlipidemic rats, the cherryenriched diet was associated with reduced fasting blood glucose, hyperlipidemia, hyperinsulinemia, and reduced fatty liver after 90 days of treatment, and also reduced several phenotypes of metabolic syndrome and both systemic and local inflammation (e.g., it decreased the retroperitoneal interleukin-6 and tumor necrosis factor-alpha activities) [14,15].…”
Section: Introductionmentioning
confidence: 99%